Bottom-up strategies for supporting self-regulation in schools: a scoping review - Ingulfsvann, Laura; Børve, Trygve; Nygård, Stig-Ivan; Mikalsen, Hilde Kristin (Frontiers in Education, 2026)
Research suggests that embodied strategies—such as physical activity, yoga, and mindfulness—may support the development of regulation skills in educational settings. However, narrow scope of previous research, methodological inconsistencies and limited theoretical grounding across studies highlight the need for more research. This review aimed to provide an explorative overview of bottom-up strategies used in school-based interventions targeting self-regulation, and to examine associated outcomes. Guided by an integrated neurobiological perspective, a systematic scoping review was conducted. Findings show that a wide range of bottom-up strategies have been implemented, with most studies reporting positive effects. Nevertheless, the field is marked by significant variation in intervention types, target populations, theoretical frameworks, and outcome measures, making it difficult to identify which strategies are most effective and for whom. Introjective practices such as yoga and mindfulness have the strongest evidence base, while other approaches—including play, dance, gross motor activities, and classroom climate interventions—remain underexplored. Importantly, none of the reviewed studies employed a whole-school approach, which could offer a more comprehensive and sustainable model for fostering regulation across subjects and stakeholders. These gaps underscore the need for more context-sensitive, theoretically grounded research to better understand which strategies work best in specific educational settings and among diverse student groups.